Ice, fire and flood: Science fiction and the Anthropocene - Milner, Andrew; Burgmann, JR; Davidson, Rjurik; Cousin, Susan (Thesis eleven, 2015)
Despite the occasional upsurge of climate change scepticism amongst conservative politicians and journalists, there is a near-consensus amongst scientists that current levels of atmospheric greenhouse gas are sufficient to alter global weather patterns to possibly disastrous effect. Like the hole in the ozone layer as described by Bruno Latour, global warming is a ‘hybrid’ natural-social-discursive phenomenon. And science fiction (SF) seems to occupy a critical location within this nature/culture nexus. This paper takes as its subject matter what Daniel Bloom dubs ‘cli-fi’. It seeks to describe how a genre defined in relation to science finds itself obliged to produce fictional responses to problems actually thrown up by contemporary scientific research. It argues against the view that ‘catastrophic’ SF is best understood as a variant of the kind of ‘apocalyptic’ fiction inspired by the Christian Book of Revelation, or Apokalypsis, on the grounds that this tends to downplay the historical novelty of SF as a genre defined primarily in relation to modern science and technology. And it examines the narrative strategies pursued in both print and audio-visual SF texts that deal with anthropogenic climate change.